CROW’S QUIZZICAL EYE: DESIGNING YOUR DESIGNING - Gregory Missingham (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2017)
A kind of personal manifesto on design thinking, this paper considers four interlaced ingredients:• that designers are Future Curious and pro-active (following Clemens Steenbergen), using thinking focused differently from science and the humanities on different fields, with different methods and values (following Nigel Cross);• that the fields and focuses of designers’ thinking are constructed within Frames (of reference), arguing with and through Philip Plowright, Sir Henry Wotton, art history and Asian landscape and aesthetic traditions, noting, also, work of Carolin Stapenhorst, Klaus Krippendorf and Christian Norberg-Schulz;• that, within continuously negotiated Frames (and their nested layers), following Kate Tregloan, the impulse a personal design epiphany provides is a product of its significance and the progress it engenders and that designers can prepare themselves to have design epiphanies both about an ongoing design and about their own designing practices,• particularly through deliberative reflective thinking, at three levels: making design conjectures, choosing design approaches and methods and, ultimately, designing their own designing.• In this paper, I am concerned with the nature of both design and designing and how what might be called ‘mature’ designers take charge of their own acts of designing, becoming Masters.